2013
DOI: 10.1186/1471-2350-14-64
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant of the atrial natriuretic peptide gene is associated with left ventricular hypertrophy in a non-diabetic population – the Malmö preventive project study

Abstract: BackgroundEpidemiological studies have shown considerable heritability of blood pressure, thus suggesting a role for genetic factors. Previous studies have shown an association of a single nucleotide polymorphism rs5068 in the NPPA locus gene with higher levels of circulating atrial natriuretic peptide as well as with lower intra individual blood pressure, but up to date, no association between rs5068 and cardiac organ damage, i.e. left ventricular hypertrophy, has been accounted for in humans. We sought to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Cannone and associates demonstrated that the minor allele of rs5068 is associated with favorable cardiometabolic phenotype including lower BMI and waist circumference in a general US population [34], findings that were replicated in a Mediterranean population, but surprisingly no association with T2D [39]. Another possible protective role of NPs have recently been observed in our study where the minor allele of rs5068 was associated with lower left ventricular mass and lower prevalence of left ventricular hypertrophy in a population free from T2D [38].…”
Section: Introductionsupporting
confidence: 70%
“…Cannone and associates demonstrated that the minor allele of rs5068 is associated with favorable cardiometabolic phenotype including lower BMI and waist circumference in a general US population [34], findings that were replicated in a Mediterranean population, but surprisingly no association with T2D [39]. Another possible protective role of NPs have recently been observed in our study where the minor allele of rs5068 was associated with lower left ventricular mass and lower prevalence of left ventricular hypertrophy in a population free from T2D [38].…”
Section: Introductionsupporting
confidence: 70%
“…15 A study conducted on a cohort of a nondiabetic Swedish population showed that subjects with the minor allele of rs5068 at the NPPA-NPPB locus, which results in higher circulating levels of ANP and BNP, 4 was associated with reduced incidence of LV hypertrophy. 16 The same genetic ANP variant also showed protection against metabolic syndrome. These findings indicate that NPs may exert multiple cardioprotective effects, mediated by NP receptors expressed in myocardium, vasculature, and in a variety of other tissues, as indicated in Figure 2.…”
Section: Natriuretic Peptides and Their Receptorsmentioning
confidence: 96%
“…In another study, deletion of 5’‐flanking region of the human NPRA gene found in Japanese patients, which reduced the transcriptional activity of the gene by 30%, appeared to increase susceptibility to hypertension and LV hypertrophy 15. A study conducted on a cohort of a nondiabetic Swedish population showed that subjects with the minor allele of rs5068 at the NPPA‐NPPB locus, which results in higher circulating levels of ANP and BNP,4 was associated with reduced incidence of LV hypertrophy 16. The same genetic ANP variant also showed protection against metabolic syndrome.…”
Section: Natriuretic Peptides and Their Receptorsmentioning
confidence: 99%
“…However, lots of candidate genes have not been confirmed in big-sample population genetic studies and Genome Wide Association Studies. In a big-sample and genome-wide meta-analysis, rs5068 variant in 3’-UTR has been inversely regulated by micro-RNA (miR)-425 and related to higher ANP levels, lower BP levels and less LV hypertrophy [ 141 ]. Rs5068 variant has also been correlated with lower anthropometric indices, lower C-reactive protein, higher high density lipoprotein, as well as less susceptibility to HF [ 142 144 ].…”
Section: Genetic Regulationmentioning
confidence: 99%